2007
DOI: 10.1038/sj.hdy.6801000
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role of natural selection in the evolution of gene regulation

Abstract: Surveys of gene expression reveal extensive variability both within and between a wide range of species. Compelling cases have been made for adaptive changes in gene regulation, but the proportion of expression divergence attributable to natural selection remains unclear. Distinguishing adaptive changes driven by positive selection from neutral divergence resulting from mutation and genetic drift is critical for understanding the evolution of gene expression. Here, we review the various methods that have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
146
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(153 citation statements)
references
References 140 publications
(175 reference statements)
5
146
0
Order By: Relevance
“…Although numerous studies of selection pressures acting on genome-wide gene expression levels have been reported (10), nearly all have found only negative selection and/or neutrality, consistent with the intuition that random changes to any functional system (including gene expression) will tend to be deleterious, and thus selected against. This is most likely because these studies were designed to detect the "average" mode of selection acting on new mutations that affect gene expression (SI Text).…”
mentioning
confidence: 88%
“…Although numerous studies of selection pressures acting on genome-wide gene expression levels have been reported (10), nearly all have found only negative selection and/or neutrality, consistent with the intuition that random changes to any functional system (including gene expression) will tend to be deleterious, and thus selected against. This is most likely because these studies were designed to detect the "average" mode of selection acting on new mutations that affect gene expression (SI Text).…”
mentioning
confidence: 88%
“…(a) Identifying adaptive phenotypic traits: insights from the transcriptome Ever since the pioneering work of Britten & Davidson (1971) and King & Wilson (1975) on the mechanisms and evolutionary role of regulatory processes, there has been increasing recognition that variation in levels of gene expression represents a major source of evolutionary novelty, which in turn can lead to phenotypic divergence by natural selection (Oleksiak et al 2002;Wittkopp 2007;Wray 2007;Fay & Wittkopp 2008). The development of microarray technologies, allowing the simultaneous detection of expression modulations at thousands of genes, offers a powerful means of assessing the importance of evolutionary change in gene regulation involved in adaptive population divergence (Bochdanovits et al 2003;Ranz & Machado 2005;Matzkin et al 2006).…”
Section: Identifying Adaptive Phenotypic Traitsmentioning
confidence: 99%
“…Recently, prospects for quantifying cis-regulatory variation have greatly improved, and, as a result, ample heritable cis-regulatory variation has been identified in many species (6); this is resulting in a growing consensus that a large amount of standing cis-regulatory variation is under weak purifying selection (7)(8)(9). Clarifying why the impact of purifying selection varies across the genome is therefore important to understand the maintenance of cis-regulatory variation.…”
mentioning
confidence: 99%